Dyeability Improvement of Cationized Corona Discharge Treated Cotton Fabric - NOURBAKHSH, SHIRIN; VALIPOUR, PEYMAN; ESMAIL YAZDANSHENAS, MOHAMMAD; GHAFFAR EBADI, ABDOL (Asian Journal of Chemistry, 2010)
In this research, cotton fabric was exposed to corona discharge at different level of passages. Un-treated and treated fabrics were cationized by a cationic agent (Levogen BF) then samples were dyed with reactive dyes (Remazol Black B, Levafix Red E4-BA). The colour parameter and colour fastness of samples were measured. The results show that by increasing passages of corona treatment up to the specified level of passages, dyed cationized corona treated cotton becomes darker (L* decreases) and in some cases, L* increases again. For remazol black B dye, cationized corona treated cotton causes to darker, less green, less blue samples and for Levafix Red E4-BA, it leads to darker, redder and less blue samples.